EXTRATERRITORIAL APPLICATION OF EU COMPETITION LAW: THE NEW STANDARDBEARER OF LEGAL IMPERIALISM? - Hüseyin Çağrı Çorlu (Ankara Avrupa Çalışmaları Dergisi)
The effects doctrine has been a major instrument in dealing with foreign conduct having repercussions on the competitiveness of national markets. The aggressive implementation of the doctrine by US courts in competition law cases has caused clamor in international community. In EU law, on the other hand, the effects doctrine had long been ignored by the CJEU, which exercised its jurisdiction on the basis of territoriality principle. In Intel, the CJEU finally endorsed the effects doctrine. This paper questioned the CJEU’s designation of the effects doctrine as a means toestablish territorial jurisdiction over extraterritorial conduct. This paper concluded that the CJEU’s approach to extraterritoriality would result in an overarching application of EU competition rules over foreign conduct.